EXPLORING NON-MUSLIM CONSUMER PREFERENCES: A COMPARATIVE ANALYSIS OF HALAL AND NON-HALAL PRODUCT ACCEPTANCE IN SURABAYA'S MODERN MARKETS - Putri, Endah Budi Permana; Nisa, Fatma Zuhrotun (UNIVERSITAS NAHDLATUL ULAMA SURABAYA, 2024)
This study explores the differences in non-Muslim consumer acceptance of halal and non-halal products in modern markets in Surabaya. The research aims to analyze the influence of price, brand reputation, and halal certification on consumer decisions. Using a comparative approach, the study identifies key factors that drive consumer preferences for both product types. The results indicate that for halal products, halal certification plays a crucial role in consumer acceptance, while for non-halal products, price and brand reputation have a more significant impact. This research highlights the importance of tailored marketing strategies, emphasizing the need for producers to consider different consumer motivations in promoting halal and non-halal products. The findings provide valuable insights for businesses targeting non-Muslim customers in the evolving Surabaya market, offering practical implications for product positioning and consumer outreach.